Editorial: Development of healthy and nutritious cereals: Recent insights on molecular advances in breeding - Swamy, B.P. Mallikarjuna; Marathi, Balram; Ribeiro-Barros, Ana I. F.; Ricachenevsky, Felipe Klein (Frontiers Media, 2021)
Worldwide more than 2 billion people are affected by micronutrient deficiencies and most of them are residing in the developing countries of Asia, Africa and Latin America (Kennedy et al., 2002). Malnutrition is linked with heavy dependence on monotonous cereal staples without much dietary diversification or nutrient supplementation. Even though significant efforts have been made over the last six decades to improve production and productivity in most food crops, it lacked associated nutritional improvement (Bouis and Welch, 2010). So, the modern varieties do not have enough variability for several nutrients, making poor rural populations vulnerable to micronutrient deficiencies. More than two dozen mineral elements, vitamins, antioxidants, and health beneficial compounds must be supplied in optimal quantities daily for normal growth and development of humans. Biofortification of cereals with elevated levels of essential micronutrients, vitamins, and reduced levels of toxic elements help to address malnutrition and is a cost-effective approach in reaching target groups, especially rural populations (Bouis and Saltman, 2017). The sustainable development goals and the Lancet Commission Report have emphasized the need for promoting nutritious diets to eradicate malnutrition (Willet et al., 2019; https://sustainabledevelopment.un.org). Among these, deficiencies of iron (Fe), zinc (Zn), and vitamin A are major global health problems. As successful examples, one high Fe rice and several high Zn rice varieties have been successfully released for commercial cultivation (Palanog et al., 2019).